2014
DOI: 10.1002/alr.21443
|View full text |Cite
|
Sign up to set email alerts
|

The safety of self‐administered allergen immunotherapy during the buildup and maintenance phases

Abstract: Background Self-administered allergen immunotherapy is considered controversial. We believe the implementation of a self-administration protocol characterized by patient preselection and a slow buildup phase is safe. Methods We analyzed 23,614 patient records and associated immunotherapy injections for systemic reactions (SR) during a 1-year period (2011 to 2012). SRs were graded in accordance with the World Allergy Organization (WAO) criteria. Results Thirty-seven SRs were reported for 23,614 patients who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 50 publications
1
8
1
1
Order By: Relevance
“…The systemic reaction rate was only 0.16% per individual and 0.002% per injection in comparison to significantly higher office-based rates of approximately 4% to 14%. 12 Consistent with these results, several other reports have previously documented the safety of self-administered or home-based SCIT. 1317 The authors concluded that the low systemic reaction rates reported showed that home-based immunotherapy was safe.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…The systemic reaction rate was only 0.16% per individual and 0.002% per injection in comparison to significantly higher office-based rates of approximately 4% to 14%. 12 Consistent with these results, several other reports have previously documented the safety of self-administered or home-based SCIT. 1317 The authors concluded that the low systemic reaction rates reported showed that home-based immunotherapy was safe.…”
Section: Discussionsupporting
confidence: 82%
“…12 The rate of allergen dose increase during the buildup phase is considered a prominent factor in immunotherapy-based systemic reactions. 9,6567 Consistent with these principles, the UAS protocol was designed to incorporate a slow buildup phase in order to diminish the associated high frequency of systemic reactions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…13,23,28 In a study involving 23,610 children and adult patients under immunotherapy, side effects have been shown to be more common in female gender and older ages. 29 There was no significant difference regarding the age group in our study, however side-effects were significantly more common in the female gender.…”
Section: Sensitivity Of the Patient Might Have Increasedcontrasting
confidence: 57%